32‐2: An Optical Compensation Scheme for High PPI AMOLED Display. Issue 1 (28th June 2022) - Han, Ying; Zhu, Mingyi; Lin, Yicheng; Li, Zhengliang; Xu, Pan; He, Jiayu; Huang, Rui; Wang, Lirong; Dong, Zhiqiang; Wang, Yu; Zhang, Xing; Quan, Wei; et al.
Abstract : This paper proposed an optical compensation scheme for a‐IGZO AMOLED with a high PPI pixel design solution. The PIN sensor is fabricated on the backplane and covers 8 sub‐pixels. The scheme is applied to a 5 inches AMOLED display. The results shows that the characteristics of a‐IGZO TFT still satisfy the needs for display. And the uniformity of the panel is improved a lot for all gray level.